2019
DOI: 10.1007/s13197-019-03728-3
|View full text |Cite
|
Sign up to set email alerts
|

Melissopalynological, physicochemical and antioxidant properties of honey from West Coast of Malaysia

Abstract: Stingless bees are native to tropical region and produce honey which are high in moisture content. Compared to honey from honeybees, there are limited studies on honey derived from stingless bees. Hence, the aim of this study was to evaluate the chemical composition and antioxidant activities of stingless bee honey. Fifteen types of honey were collected from six states in West Coast of Malaysia and pollen analyses were carried out. Four types of unifloral honey samples produced by stingless bees were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 45 publications
3
36
2
4
Order By: Relevance
“…Total flavonoid amount of samples are similar compared to the results reported in the literature (Meda et al, 2005;Šarić et al, 2012) and lower than Moniruzzaman et al (2014) and Al-Farsi et al (2018). The total phenolic amount of our findings was similar to Boussaid et al (2018), while the total flavonoid content was higher than Boussaid et al (2018) and Selvaraju et al (2019).…”
Section: Discussionsupporting
confidence: 90%
“…Total flavonoid amount of samples are similar compared to the results reported in the literature (Meda et al, 2005;Šarić et al, 2012) and lower than Moniruzzaman et al (2014) and Al-Farsi et al (2018). The total phenolic amount of our findings was similar to Boussaid et al (2018), while the total flavonoid content was higher than Boussaid et al (2018) and Selvaraju et al (2019).…”
Section: Discussionsupporting
confidence: 90%
“…Myrtaceae plants are known to be visited by many stingless bees as noted by Antonini et al (2006), and this phenomenon was emphasized by do Nascimento et al (2015) who mentioned that pollen spectrum of honey produced by stingless bees from Brazil showed significant representation of Myrtaceae pollen. The presence of Myrtaceae pollen in honey samples produced by stingless bees from melissopalynological studies in neighboring countries has also been reported such as in Thailand by Thakodee et al (2018) who found pollen of Melaleuca quinquenervia and Syzygium jambos and from West Coast of Malaysia by Selvaraju et al (2019) who found pollen of Baeckea crassifolia and Psidium guajava.…”
Section: Variation In Number and Composition Of Plant Species And Fammentioning
confidence: 72%
“…Another pollen type found in considerable percentage was from coconut tree (Cocos nucifera) which grows around the nest. The occurrence of C. nucifera pollen at notable amount was due to the preference of stingless bee to forage on flowers with high sugar concentration which are available throughout the year (Selvaraju et al 2019). The pollen composition in honey indicated that T. laeviceps forage for foods from plants close to the hives as long as they remain available.…”
Section: Variation In Number and Composition Of Plant Species And Fammentioning
confidence: 99%
See 1 more Smart Citation
“…Uji keaslian madu dilihat dari aspek metode yang digunakan secara garis besar dibagi menjadi dua, yaitu metode klasik dan metode modern (Chin & Sowndhararajan 2020). Metode klasik untuk uji keaslian madu meliputi metode analisis physicochemical dan metode melissopalynological (Selvaraju et al 2019;Puścion-Jakubik et al 2020;El-Sofany et al 2020). Meskipun sangat akurat, metode klasik memiliki banyak kelemahan, seperti waktu analisis yang sangat lama, sangat melelahkan dan melibatkan seorang analis yang sangat ahli untuk mengidentifikasi serbuk sari setiap madu serta adanya potensi ketidakkonsistenan (Oddo & Bogdanov 2004).…”
Section: Pendahuluanunclassified